2000
DOI: 10.1038/sj.bjp.0703719
|View full text |Cite
|
Sign up to set email alerts
|

The role of M2‐muscarinic receptors in mediating contraction of the pig urinary bladder in vitro

Abstract: 1 In urinary bladder, M 2 -muscarinic receptors predominate, but it is the smaller population of M 3 -receptors which mediate detrusor contraction. This study examines the M 2 : M 3 ratio and the role of M 2 -receptors in contraction of pig urinary bladder. 4 On normal detrusor in vitro, 4-DAMP and methoctramine caused surmountable antagonism of responses to carbachol with pK B values of 9.37+0.07 and 6.05+0.05 respectively. Darifenacin caused unsurmountable antagonism, the apparent pK B value being 8.61+0.10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…These data demonstrate that contraction of human bladder in response to carbachol is mediated predominantly if not exclusively by the M 3 muscarinic receptor. This situation mimics closely the previously reported ®ndings in rats (Choppin et al, 1998;Hegde et al, 1997;Longhurst et al, 1995;Longhurst & Levendusky, 2000;Tong et al, 1997), mice (Choppin & Eglen, 2001b), pigs (Yamanishi et al, 2000) and dogs (Choppin & Eglen, 2001a). These data suggest that a drug for the e ective treatment of overactive bladder should have high a nity for M 3 receptors.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…These data demonstrate that contraction of human bladder in response to carbachol is mediated predominantly if not exclusively by the M 3 muscarinic receptor. This situation mimics closely the previously reported ®ndings in rats (Choppin et al, 1998;Hegde et al, 1997;Longhurst et al, 1995;Longhurst & Levendusky, 2000;Tong et al, 1997), mice (Choppin & Eglen, 2001b), pigs (Yamanishi et al, 2000) and dogs (Choppin & Eglen, 2001a). These data suggest that a drug for the e ective treatment of overactive bladder should have high a nity for M 3 receptors.…”
supporting
confidence: 90%
“…A similar situation is found in the bladder of rats, rabbits, guinea-pigs (Wang et al, 1995) and pigs (Goepel et al, 1998;Yamanishi et al, 2000). The contractile response to the exogenous muscarinic agonist carbachol and to endogenous agonist released by ®eld stimulation, however, occurs predominantly if not exclusively via M 3 receptors in rats (Choppin et al, 1998;Hegde et al, 1997;Longhurst et al, 1995;Longhurst & Levendusky, 2000;Tong et al, 1997), mice (Choppin & Eglen, 2001b), pigs (Yamanishi et al, 2000) and dogs (Choppin & Eglen, 2001a).…”
supporting
confidence: 56%
“…M 2 and M 3 receptor subtypes predominate in the detrusor muscle, with the population of the M 2 subtype receptor in detrusor muscle greater than the M 3 subtype. Previous immunoprecipitation data with subtype-selective antibodies and radioligand binding studies have reported a ratio of M 2 to M 3 receptors in the detrusor to be approximately three to one for human, guinea pig, and rabbit bladders and selective radioligand binding data indicates a similar ratio for the pig bladder [Yamanishi et al, 2000]. Despite higher density of M 2 receptors, contraction has been found to be primarily mediated by M 3 receptors under normal conditions in all species studied.…”
Section: Introductionmentioning
confidence: 71%
“…M 2 and M 3 muscarinic receptors coexist in the bladder of various mammalian species, including humans, but the expression of M 2 receptors is much greater than that of the M 3 receptors (Wang et al, 1995;Goepel et al, 1998;Yamanishi et al, 2000;Kories et al, 2003). Nevertheless, the contractile response to the exogenous agonist carbachol and to endogenous agonist released by field stimulation have been attributed predominantly if not exclusively to M 3 receptors in rats (Longhurst et al…”
Section: In Contrast Trans-4-[(1r)-1-aminoethyl]-n-4-mentioning
confidence: 99%